2018
DOI: 10.1021/acsami.8b17636
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Functionalized With Graphene Oxide Enhanced Biomimetic Mineralization and in Situ Bone Defect Repair

Abstract: Biomimetic mineralization using simulated body fluid (SBF) can form a bonelike apatite (Ap) on the natural polymers and enhance osteoconductivity and biocompatibility, and reduce immunological rejection. Nevertheless, the coating efficiency of the bonelike apatite layer on natural polymers still needs to be improved. Graphene oxide (GO) is rich in functional groups, such as carbonyls (−COOH) and hydroxyls (−OH), which can provide more active sites for biomimetic mineralization and improve the proliferation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 44 publications
4
58
0
Order By: Relevance
“…It has been shown that the incorporation of GO and GQD into aliphatic polyesters can also induce the deposition of apatite crystals on their surfaces [76,228]. The oxygenated groups of GO such as carboxyl (−COOH) and hydroxyl (−OH) provide active sites for biomineralization [228,252]. For instance, a thick layer of calcium phosphate mineral can be deposited on electrospun PCL/0.3 wt% GO mat surface by immersion in 10 SBF solution at room temperature for 20 h [228].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…It has been shown that the incorporation of GO and GQD into aliphatic polyesters can also induce the deposition of apatite crystals on their surfaces [76,228]. The oxygenated groups of GO such as carboxyl (−COOH) and hydroxyl (−OH) provide active sites for biomineralization [228,252]. For instance, a thick layer of calcium phosphate mineral can be deposited on electrospun PCL/0.3 wt% GO mat surface by immersion in 10 SBF solution at room temperature for 20 h [228].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…In addition, Zhang et al proposed a GO-based fluorescent nanosensor that can be used to quickly detect telomerase content in cells and image telomerase (Zhang et al, 2018). Zhou et al studied a new method of introducing GO into bone tissue to enhance biomineralization, and they found that when the GO concentration was 0.1% w/v and immersed in simulated body fluids for 7 days, GO-collagen-apatite 3D scaffold showed good therapeutic effect in repairing skull defects in rats (Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, graphene oxide (GO) with excellent light-absorbing property and photothermal conversion efficiency has been widely used for PTT application [20,25]. Moreover, the carbonyl, epoxy and hydroxyl groups in the GO can serve as bioactive sites for cell proliferation and bone mineralization via activating MAPK signaling pathway [26][27][28]. It is reasonably inferred that the GO-modified scaffolds are fit for PTT against tumors and subsequent bone defect healing.…”
Section: Introductionmentioning
confidence: 99%